Industrial research versus development investment: the implications of financial constraints - Dirk Czarnitzki; Hanna Hottenrott; Susanne Thorwarth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Previous literature provided evidence on financing constraints for investment in R&D activities due to capital market imperfections and special features of R&D investments. Moreover, it has been shown that a shift in capital structure towards more debt, results in a reduction of R&D investments. This article complements this literature by compartmentalizing R&D activities in its components, R and D. In particular, we distinguish research from development as these activities do not only differ in their nature, but also to a large extent take place sequentially. Our results show that R investment is more sensitive to the firms' operating liquidity than D indicating that firms have to rely even more on internal funds for financing their research compared to development activities. Moreover, we find that (basic) research subsidy recipients' investment is less sensitive to internal liquidity.
Keywords: O31; O32; O38; 330; Research and development; liquidity constraints; innovation policy; Industrielle Forschung; Forschungsfinanzierung; Verschuldungsrestriktion; Innovation; Finanzierung; Innovationspolitik; Deutschland